1985
DOI: 10.5006/1.3582988
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulfate Corrosion in Paper-Machine White Water

Abstract: Potentiostatic, potentiodynamic, and immersion tests were conducted on a range of alloys used in paper-machine service. It was found that thiosulfate contamination of white water can cause pitting in AISI 304 and CA-15 stainless steels (SS), and, by comparison, salts such as NaCl, Na2SO, and Al2(SO4)3 are much less corrosive. For sensitized AISI 304, thiosulfate levels in the range of 3 to 75 ppm cause pitting, 5 to 20 ppm S2O3= being particularly aggressive. Thiosulfate pitting occurred in the absence of chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…5 Localized corrosion of SS in S 2 O 3 2--containing environments has been studied extensively. [6][7][8][9][10][11][12][13][14][15][16][17] Thiosulfate pitting is known to occur in a limited potential range 6 and molar ratio ([Cl -] + sulfate [SO 4 2-])/[S 2 O 3 2-]. 7 The most sensitive potential range for thiosulfate pitting is at 0 mV vs saturated calomel electrode (SCE) to -400 mV SCE 8 and at molar ratio 10 to 30.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5 Localized corrosion of SS in S 2 O 3 2--containing environments has been studied extensively. [6][7][8][9][10][11][12][13][14][15][16][17] Thiosulfate pitting is known to occur in a limited potential range 6 and molar ratio ([Cl -] + sulfate [SO 4 2-])/[S 2 O 3 2-]. 7 The most sensitive potential range for thiosulfate pitting is at 0 mV vs saturated calomel electrode (SCE) to -400 mV SCE 8 and at molar ratio 10 to 30.…”
Section: Introductionmentioning
confidence: 98%
“…Sensitized UNS S30403 was prone especially to pitting at SO 4 2-/S 2 O 3 2molar ratios from 6 to 23 (100 mg/L SO 4 2-, pH 4.5, 50°C, 5 mg/L to 20 mg/L S 2 O 3 2-) at potentials from 0 mV SCE to -300 mV SCE , while unsensitized UNS S30403 experienced thiosulfate pitting at higher potential levels, 100 mV SCE to -100 mV SCE . 8 In the absence of Cl -, other anions like SO 4 2-, may form hydrolyzed metal compounds and maintain or increase acidity inside the pit.…”
Section: Introductionmentioning
confidence: 99%
“…Thiosulfate increases the possible potential range of corrosion pits to grow by lowering the repassivation potential. Hydrogen sulfide originating from thiosulfate is proposed to accelerate the anodic dissolution inside corrosion pits and crevices by forming sparingly soluble metal sulfides and by acidifying the local environment [Garner (1985)]. …”
Section: Fig 4 Optical Microscopic Photographs Of Pits Formed On 304mentioning
confidence: 99%
“…It is suggested that these cracks can be formed due to the work hardening that can transform a part of the austenite phase to the martensite during the fatigue test. The martensite phase is considered a hard phase and fractured in a brittle manner and sometimes causes micro-cracks inside the metal [Garner (1985)]. …”
Section: Fatigue Behavior Of Ss 304mentioning
confidence: 99%
“…0ϭٌ· Jϭٌ· (Ϫsٌf) ииииииииииииииииииииииииииииииииииииииииииии( 3 ) 13) J c иииииииииииииииииииииииииииииииии ( 6 ) f 0,steel ϭϪ0.059 log(gm NaCl )Ϫ0.5105 ииииииииииииииииииииииииии ( 7 ) f 0,zinc ϭϪ0.059 log(gm NaCl )Ϫ1.0242 ииииииииииииииииииииииииии( 8 )…”
unclassified